Improving mechanical properties and high-temperature oxidation of press hardened steel by adding Cr and Si - Zhu, Rong; Yang, Yonggang; Zhang, Baozhong; Zhang, Borui; Li, Lei; Wu, Yanxin; Mi, Zhenli (International journal of minerals, metallurgy and materials, 2024)
This work investigated the effect of Cr and Si on the mechanical properties and oxidation resistance of press hardened steel. Results indicated that the microstructure of the Cr–Si micro-alloyed press hardened steel consisted of lath martensite, M 23 C 6 carbides, and retained austenite. The retained austenite and carbides are responsible for the increase in elongation of the micro-alloyed steel. In addition, after oxidation at 930°C for 5 min, the thickness of the oxide scales on the Cr–Si micro-alloyed press hardened steel is less than 5 µm, much thinner than 45.50 µm-thick oxide scales on 22MnB5. The oxide scales of the Cr–Si micro-alloyed steel are composed of Fe 2 O 3 , Fe 3 O 4 , mixed spinel oxide (FeCr 2 O 4 and Fe 2 SiO 4 ), and amorphous SiO 2 . Adding Cr and Si significantly reduces the thickness of the oxide scales and prevents the generation of the FeO phase. Due to the increase of spinel FeCr 2 O 4 and Fe 2 SiO 4 phase in the inner oxide scale and the amorphous SiO 2 close to the substrate, the oxidation resistance of the Cr–Si micro-alloyed press hardened steel is improved.